# Solve for y 0.12(y-8)+0.04y=0.06y-0.01*60 0.12(y-8)+0.04y=0.06y-0.01⋅60
Simplify 0.12(y-8)+0.04y.
Simplify each term.
Apply the distributive property.
0.12y+0.12⋅-8+0.04y=0.06y-0.01⋅60
Multiply 0.12 by -8.
0.12y-0.96+0.04y=0.06y-0.01⋅60
0.12y-0.96+0.04y=0.06y-0.01⋅60
Add 0.12y and 0.04y.
0.16y-0.96=0.06y-0.01⋅60
0.16y-0.96=0.06y-0.01⋅60
Multiply -0.01 by 60.
0.16y-0.96=0.06y-0.6
Move all terms containing y to the left side of the equation.
Subtract 0.06y from both sides of the equation.
0.16y-0.96-0.06y=-0.6
Subtract 0.06y from 0.16y.
0.1y-0.96=-0.6
0.1y-0.96=-0.6
Move all terms not containing y to the right side of the equation.
Add 0.96 to both sides of the equation.
0.1y=-0.6+0.96
Add -0.6 and 0.96.
0.1y=0.36
0.1y=0.36
Divide each term by 0.1 and simplify.
Divide each term in 0.1y=0.36 by 0.1.
0.1y0.1=0.360.1
Cancel the common factor of 0.1.
y=0.360.1
Divide 0.36 by 0.1.
y=3.6
y=3.6
Solve for y 0.12(y-8)+0.04y=0.06y-0.01*60

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top